Pengaruh Independensi, Kompetensi, Pengalaman Kerja, Due Professional Care Dan Akuntabilitas Terhadap Kualitas Audit(Studi Empiris Pada Auditor Kap Di Wilayah Surakarta Dan Yogyakarta) - Akhmadi, Turbin, Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2015)
This research is aimed to examine the influence of Independence, competence, work experience, Due professional care and Accountability to the quality of audits. The population in this research is all auditors at the KAP in Surakarta and Yogyakarta. Sample collection method using a convenience sampling. The analytical tool used include normality test, multicoloniarity, heteroscedasticity test, coefficient determination test, F test and t test. The results showed that the coefficient of determination obtained value of 0.806, which means that 80.6% of audit quality is affected by the variable independence, competence, work experience, professional due care and accountability. The remaining 19.4% is influenced by variables outside the model. T test results showed competence and work experience variables statistically significant effect on audit quality, while variable independency, due professional care and accountability no effect on audit quality. Key words: independence, competence, work experience, Due professional care, Accountability, quality of audits.